2018
DOI: 10.3390/app8020190
|View full text |Cite
|
Sign up to set email alerts
|

Early Age Carbonation of Fiber-Cement Composites under Real Processing Conditions: A Parametric Investigation

Abstract: This paper presents the outcome of a comprehensive experimental program undertaken to study the performance of cellulose pulp and synthetic PVA (polyvinyl alcohol) based fiber-cement composite under both carbonated and non-carbonated curing conditions at early age. The composites were produced at different rolling pressures (2.5 to 9.0 bar) and subjected to various curing conditions in which the effects of CO 2 pressure (1 to 3 bar) and curing time (3 to 9 h) were studied. The mechanical properties (modulus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In general, vegetated concrete has a high porosity. Indeed, the SEM pictures of a significant variety of fibre cements in the literature exhibit several fields when compared to regular concrete [ 82 , 83 , 84 , 85 , 86 ]. As a result, the addition of wood fibres to concrete enhances its density.…”
Section: Resultsmentioning
confidence: 99%
“…In general, vegetated concrete has a high porosity. Indeed, the SEM pictures of a significant variety of fibre cements in the literature exhibit several fields when compared to regular concrete [ 82 , 83 , 84 , 85 , 86 ]. As a result, the addition of wood fibres to concrete enhances its density.…”
Section: Resultsmentioning
confidence: 99%
“…27 Kottititum et al found that when the curing pressure was increased from 1 to 3 bar (0.1-0.3 MPa), the modulus of rupture of ber-cement composites increased by 16%, the modulus of elasticity increased by 23%, and the toughness decreased by 51%. 28 Tu et al observed that CO 2 pressure (0.01 and 0.4 MPa) impacted the crystalline of CaCO 3 for cement specimens mixed with limestone powder. 29 Extensive reports have supported the multiple benets of carbonation to CBMs at early ages in terms of CO 2 sinking and engineering performance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The ASC process usually takes about 24 h (1 day) by using the curing temperature between 160℃ to 180°C and pressure between 8 bar to 12 bar. [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%